Jaminan Mutu Loin Center Cut Beku dalam Memenuhi Standar Nasional dan Persyaratan Ekspor Pada Perusahaan XYZ di Bali - I Gusti Ayu Budiadnyani; I Made Aditya Nugraha; I Gede Riyan Mahayana (Universitas Mataram, 2026)
This study aims to assess the quality of frozen loin center cut products in relation to the Indonesian National Standard (SNI) and export requirements, considering the increasing demand for quality and food safety in international markets. A descriptive quantitative approach was employed through direct observation, interviews, and analysis of primary and secondary data collected from a fish processing industry in Bali. Quality evaluation was conducted based on organoleptic, chemical, and microbiological parameters. The results indicate that the production process was carried out systematically by implementing proper fish handling practices, including a consistent cold chain system and appropriate stock management. Organoleptic assessment showed that the product had excellent quality with a high level of freshness. Chemical analysis revealed low histamine levels in both raw materials and final products, indicating effective temperature control and handling during processing. Microbiological testing demonstrated that total plate counts and pathogenic bacteria such as Escherichia coli and Salmonella spp. were within acceptable limits, confirming good sanitation and hygiene practices. Overall, the evaluated parameters comply with SNI and export standards, indicating that the product is safe and suitable for international markets. However, histamine content and microbiological contamination remain critical factors that require strict control to ensure consistent product quality. This study highlights the importance of maintaining cold chain integrity, sanitation, and quality control systems to enhance competitiveness in the global seafood market.